Reef shallowing is a critical control on benthic foraminiferal assemblage composition on nearshore turbid coral reefs - Johnson, J. A. (2019)
Declining water quality represents a major threat to the coral reefs of Australia's Great Barrier Reef (GBR). Due to their close proximity to river point sources, reefs situated on the inner-shelf of the GBR are widely perceived to be most susceptible to the increased discharge of nutrients and sediments from coastal catchments, many of which have been modified since European settlement. However, the impact and magnitude of water quality change on the GBR's inner-shelf reefs remains unclear. Much of the uncertainty can be attributed to a paucity of long-term records with which to assess ecological and environmental change over appropriate reef-building timescales. Here, we present benthic foraminiferal palaeo-records from three proximal nearshore turbid-zone reefs located within the central region of the GBR. Bayesian age-depth modelling was used to identify the core intervals corresponding to the timing of European settlement in the region (c. 1850 CE), enabling the investigation of: (1) the composition and variability of benthic foraminiferal assemblages during reef shallowing towards sea level; and (2) whether any signal of increased nutrient and sediment inputs, as the result of historical land-use change, can be discerned on the most nearshore reefs of the central GBR. Multivariate analyses identified two assemblage groups, delineated by a significant increase in the relative abundance of Pararotalia spp. up-core. Our results suggest that post-European settlement associated increases in nutrient and sediment inputs are unlikely to have driven the observed shifts in benthic foraminiferal assemblage composition. Rather, we interpret changes in the composition of benthic foraminiferal assemblages as being linked to changes in hydrodynamic energy, light availability and the carbonate content of reef-matrix sediments during reef shallowing towards sea level. Our findings support the hypothesis that nearshore turbid-zone reefs have a higher resistance to increased nutrient and sediment inputs than those located further offshore, towards the inner/mid-shelf boundary of the GBR.